Pharmaceutical Formulations to Increase Gastric Residence Time: Concepts and Strategies - Radhakrishnan, Praveen; Singh, Sandeep K.; Verma, Priya R.P. (Drug Delivery Letters, 2017)
Background and Objective: Gastroretentive dosage forms have emerged as efficient means for oral controlled delivery of several drugs. The objective of this review is to bring under one umbrella, all the necessary knowledge regarding gastroretentive dosage forms, especially floating dosage forms. Methods: The review covers basic anatomy and physiology of gastrointestinal tract, gastric emptying and related problems in drug absorption, candidate drugs and drugs unsuited for gastroretentive formulations, pharmacokinetics of gastroretentive formulations and factors affecting gastric residence time of dosage forms. Various approaches coined by different researchers to achieve prolonged gastric residence time like low density floating systems, high density sinking systems, modified shape systems, size controlled systems, muco-adhesive systems and magnetic systems are also detailed. Special emphasize is given to floating dosage forms, their advantages, disadvantages, excipients used in the formulation, critical parameters and methods of evaluation. Conclusion: The article is expected to motivate the researchers to investigate on gastroretentive dosage forms systematically.
Keywords: bioavailability